2018
DOI: 10.1093/nar/gky1186
|View full text |Cite|
|
Sign up to set email alerts
|

Structural insights into chromosome attachment to the nuclear envelope by an inner nuclear membrane protein Bqt4 in fission yeast

Abstract: The dynamic association of chromosomes with the nuclear envelope (NE) is essential for chromosome maintenance. Schizosaccharomyces pombe inner nuclear membrane protein Bqt4 plays a critical role in connecting telomeres to the NE, mainly through a direct interaction with the telomeric protein Rap1. Bqt4 also interacts with Lem2 for pericentric heterochromatin maintenance. How Bqt4 coordinates the interactions with different proteins to exert their functions is unclear. Here, we report the crystal structures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…(D-E) Wild-type, csi1Δ or lem2Δ csi1Δ cells with Sad1-GFP (yellow) and Ppc89-mCherry (magenta) were grown for 4 h at 25°C or 36°C and then imaged. Bqt4 (Hirano et al, 2018;Hu C et al, 2019); Cmp7 (Gu et al, 2017) and Ima1 (Hiraoka et al, 2011;Steglich et al, 2012). The only single gene deletion mutant to significantly affect Sad1 ring formation was csi1Δ, where we observed a 29.6% reduction in ring formation at 36°C ( Fig 3D-E, Fig S1C).…”
Section: Centromeric-spb Linkage Proteins Lem2 and Csi1 Contribute Tomentioning
confidence: 54%
“…(D-E) Wild-type, csi1Δ or lem2Δ csi1Δ cells with Sad1-GFP (yellow) and Ppc89-mCherry (magenta) were grown for 4 h at 25°C or 36°C and then imaged. Bqt4 (Hirano et al, 2018;Hu C et al, 2019); Cmp7 (Gu et al, 2017) and Ima1 (Hiraoka et al, 2011;Steglich et al, 2012). The only single gene deletion mutant to significantly affect Sad1 ring formation was csi1Δ, where we observed a 29.6% reduction in ring formation at 36°C ( Fig 3D-E, Fig S1C).…”
Section: Centromeric-spb Linkage Proteins Lem2 and Csi1 Contribute Tomentioning
confidence: 54%
“…Further, single point mutation analyses suggested that phosphorylation at Ser496 is critical for the Rap1–Bqt4 interaction (Figure 3C). It should be noted that Ser496 is located within the interface of the Bqt4-binding domain of Rap1 (490–513 a.a.) (29). Furthermore, Rap1-7A showed lower affinity for GST-Bqt4 2-181 , compared to that of wild-type Rap1 or Rap1-7E, in S. pombe cell lysates (Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
“…This study indicates that of the seven putative phosphorylation sites, the phosphorylation of Ser496 is the most important for the regulation of both Rap1–Bqt4 and Rap1–Poz1 interactions. Ser496 resides within the Bqt4-interacting interface (490–513 a.a.) (29). Although Ser496 lies just outside of the Poz1-interacting interface (467–491 a.a.) (28), the longer region of Rap1 (467–496 a.a.) was required for production of high-quality crystals of the Rap1–Poz1–Tpz1 complex (27), suggesting that phosphorylation of Ser496 can influence the Rap1-Poz1 interaction.…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal LEM domain contributes to centromere association and clustering at the NE, whereas the C-terminal MSC domain is required for telomere anchoring and heterochromatin silencing (Barrales et al, 2016). In addition, a small region located adjacent to the first transmembrane domain was shown to interact with the integral membrane protein Bqt4 (Hirano et al, 2018;Hu et al, 2019). We assessed the role of the N-and Cterminal Lem2 regions in Red1 binding using truncated mutants (Lem2-∆N and Lem2-∆MSC, respectively; Fig.…”
Section: Lem2 Interacts With Exosome-targeting Factor Red1mentioning
confidence: 99%